Criticism of modern architectural theories : lecture notes - Timokhin, V. O.; Bulakh, I. V. (КНУБА, 2021)
The main features, trends and styles in the development of modern architectural theory and practice are considered. Designed for foreign students studying in the direction of preparation 19 "Architecture and Construction", specialty 191 "Architecture and Urban Planning". Розглянуто основні особливості, напрямки, течії та стилі в розвитку сучасної архітектурної теорії та практики. Призначений для студентів, які навчаються за напрямом підготовки 19 "Архітектура та будівництво", спеціальність 191 "Архітектура та містобудування".
Keywords: сучасна архітектура; 72.02:721